Myoepithelioma in Mandibular Gingiva: A Rare Case Report - Hideki Mori; Noriko Matsuzawa; Yosuke Jinno; Yoshihiro Kimura; Mitsuhiro Aoki (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Myoepithelioma is an uncommon benign salivary gland tumor. Most of the myoepitheliomas develop in the parotid gland. Myoepitheliomas also occur in the minor salivary gland, such as hard & soft plates, buccal mucosa, and nasal septum or cavity. Case presentation: We report here a rare case of myoepithelioma arising from the minor salivary gland of the mandibular gingiva in a 39-year-old female. Gingival myoepithelioma is extremely rare. To the best of our knowledge, only one case of gingival myoepithelioma has been described. She presented with a dark purple, elastic nodule of 1cm in size. The MRI T2 revealed a heterogeneous nodular shadow with an internal high signal intensity in the right mandibular retromolar region. A total excision of the lesion to remove the nodule was successfully carried out under general anesthesia. The tumor was a well-defined, smooth-surfaced, and encapsulated mass.　Histologically, the myoepithelioma is composed principally of spindle-shaped cells. Besides them, scattered clusters of epithelioid and clear cells with microcystic spaces were present. Immunohistochemically, cytokeratin 14, being regarded as a representative marker for myoepithelial cells, was distinctively positive. She has shown no recurrence two years after surgery, although myoepithelioma generally has a low recurrence rate, and malignant transformation is rare. Conclusion: We report a rare case of extrasalivary gland neoplasm composed of myoepithelial cells arising from the gingiva of the right mandibular retromolar region, with the clinical and pathological characteristics of the present case regarding previously reported cases.